Strategy in Teaching Vocabulary at Kindergarten - Nurhidayah Sari; Lusi Maleni; Muhammad Rafiq; Rinaldi Setiawan (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This research aimed to investigate the general application of vocabulary teaching strategies for young learners in kindergarten. A qualitative research with observation, oral interviews are used it as a useful instrument for data collection. Observation-based surveys aim to identify the general strategy of teaching vocabulary to young learners, a common difficulty usually encountered in teaching vocabulary. Oral interviews are used to elaborate information collected from observations and find out the teacher's views on how to solve problems that arise in kindergarten classrooms, especially teaching the vocabulary section. The results of this study show that the use of images and media-realia in presentation, using questions and answers to young learners as practice and a short answer in vocabulary revision is the strategy the most preferred by many kindergarten teachers in teaching young learners in teaching vocabulary.. The teacher also explained that they had adjusted the strategy if it was deemed inappropriate; a combination of things must be considered. On the other hand, most teachers have revealed that they have experienced certain difficulties such as the lack of focus of young learners when the teacher explained or introduced new vocabulary to young learners because English was still a foreign language for young learners in kindergarten. However, most of the difficulties can be overcome. The researcher also added general strategies used in teaching vocabulary, namely Flashcards, Games, Using Visual Representations, Word Maps, Frayer Models, Stories, Context Clues, Possible Sentences. Therefore, this study identifies providing games in the class is very useful for the learning process of vocabulary in kindergarten.